CASH SALES ON ADMINISTRATIVE APPLICATIONS MUTIARA DEPOK HOUSING USING MICROSOFT VISUAL BASIC 6.0 - Nunun Widyaharti; Jalinas, Skom, MM Jalinas, Skom, MM (Jurnal Sistem Informasi, 2002)
Speed and accuracy in data processing is further enhanced, so information needed canbe obtained with a relatively short time. Not happening duplicate data within thepresentation of information.Effectiveness and efficiency will be created, so that it can assist in planning anddecision making for managers.